A Model for the Long-Run Theory of Value - Newman, Peter; Wolfe, J. N. (Review of Economic Studies, 1961)
Peter Newman, J. N. Wolfe; A Model for the Long-Run Theory of Value1, The Review of Economic Studies, Volume 29, Issue 1, 1 October 1961, Pages 51–61, http